Anna Dessert Online Ordering System (ADOOS) / Mohd Fahridzal Hashim - Hashim, Mohd Fahridzal (2023)
The evolution of the internet and technologies has created a great advancement in the E-Business and E-Commerce world. One of the sectors that receive a great impact because of the advancements of the internet and technologies is the food industry. Online ordering systems are very common nowadays for the food industries player. In order to compete in the market, an online ordering system is not merely for big companies, but it is also needed by small and medium companies. This project represents the process of creating an online ordering system for Anna Dessert. The system is called Anna Dessert Online Ordering System (ADOOS). The purpose of this system is to help solve the current problem that they are having with their current ordering process. The development of this system is to help Anna Dessert to further grow its business and to provide quality services to all its customers. ADOOS was developed using an adapted evolutionary prototyping model that consists of seven phases. This methodology was selected as it provides better risk analysis, and the initial operating time is much lesser than the other model. Adopting this model, the current business process and the problem of Anna Dessert were identified through the process of interviewing the owner. The design and development of ADOOS bring improvement to the current process of Anna Dessert. ADOOS give Anna Dessert’s customers the ability to make an order anytime and anywhere plus it helps to solve issues on their current process of ordering. The functionality of ADOOS was also tested to make sure that the system's functionality is operating as required. In terms of the future, further improvements can be done such as offering more variety of payment options and also providing more advanced delivery tracking.